Strategi Dinas Sosial Takalar Dalam Pemberdayaan Fakir Miskin Melalui Program Kelompok Usaha Bersama (KUBE) - Nur Fadilah Ramadhani; St. Nasriah; Muh. Anwar (Jurnal Berita Sosial, 2023)
This type of research uses descriptive qualitative research using a sociological approach method. Data sources in this study are based on primary data sources, namely 2 from the Takalar Social Service in the field of handling the poor and 2 recipients of KUBE program assistance. Secondary data sources in this study used literature list studies through books, articles and scientific papers. This research instrument is a researcher who descends directly by using several field instruments in collecting data, namely through observation, interviews and documentation. After all the data was collected, the researcher analyzed the data with data reduction, data presentation and conclusion drawing. The results showed that the strategy of the social service of Takalar district in empowering the poor through the KUBE program, namely: (a) socialization of the joint business group program (KUBE), (b) formation of joint business groups (KUBE), (c) implementation of the joint business group program (KUBE), (d) counseling on business skills for joint business group recipients (KUBE), (e) allocation of joint business group program funds (KUBE) and (f) monitoring and evaluation of joint business group programs (KUBE), (g) program assistance personnel (KUBE). The constraints of the Takalar district social service in empowering the poor through the joint business group program (KUBE) are: (a) lack of joint business group program assistants (KUBE), (b) not maximizing socialization in the joint business group program (KUBE) and (c) not maximizing the skills counseling of the joint business group program (KUBE).